Влияние параметров электроразрядного контура с индуктивно-емкостным накопителем энергии на характеристики электрического разряда - Дубовенко, К.В. (Електротехніка і електромеханіка, 2012)
Numerical simulation of high power air spark discharge characteristics in a circuit with an inductive-capacitive energy store and a foil blasting release has been carried out with a magnetohydrodynamic approach application. Influence of the discharge circuit parameters (the plasma channel length, voltage of the plasma load connection to the discharge circuit, inductor store inductance) on the spark characteristics has been determined.